2013
DOI: 10.1063/1.4821966
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants and dispersion energy parameters of NiO thin films prepared by radio frequency magnetron sputtering technique

Abstract: In this paper, we report on rf power induced change in the structural and optical properties of nickel oxide (NiO) thin films deposited onto glass substrates by rf magnetron sputtering technique. The crystallinity of the film was found to increase with increasing rf power and the deposited film belong to cubic phase. The maximum optical transmittance of 95% was observed for the film deposited at 100 W. The slight shift in transmission threshold towards higher wavelength region with increasing rf power revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(52 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…It reveals that the optical band gap of the MoO 3 film decreases with the increase of the annealing temperature that might be due to the formation of oxygen ion vacancies and the improvement of crystallinity in the film. 11 This presumption is consistent with our XRD finding. The optical band gap value …”
Section: Optical Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…It reveals that the optical band gap of the MoO 3 film decreases with the increase of the annealing temperature that might be due to the formation of oxygen ion vacancies and the improvement of crystallinity in the film. 11 This presumption is consistent with our XRD finding. The optical band gap value …”
Section: Optical Propertiessupporting
confidence: 83%
“…The film annealed at 400 C exhibits only 65% of transparency at 575 nm due to the free carrier absorption and scattering of light by formation of micro crystallites. 11 The optical behavior of the film annealed at 350 C is different from the others indicating the phase transformation around 300 C which causes more absorption by charge carriers. The higher transmittance in the higher wavelength region indicates the decrement in optical band gap (E g ) with the increase of the annealing temperatures.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…It is found that the increase in rf power leads to a decrease in optical band gaps from 3.53 to 3.45 eV. WenTing et al [25] and Usha et al [26] were obtained decreasing band gap with increasing rf power. Suzuki et al [27] reported the band gaps of 4.1-2.6 eV for CeO 2 thin films.…”
Section: Optical Studiesmentioning
confidence: 92%
“…[2,4,6,7]. A variety of NiO film deposition techniques has been investigated including sputtering, pulsed laser deposition, reactive evaporation, spray pyrolysis, thermal deposition, and metal-organic chemical vapor deposition (MOCVD) [1,4,8,[9][10][11]. As it has been reported [12] NiO films obtained are predominantly amorphous or randomly oriented polycrystalline.…”
Section: Introductionmentioning
confidence: 98%
“…Nickel oxide (NiO) films have attracted considerable interest of researchers due to their semitransparent, thermoelectric, and catalytic properties [1]. NiO is considered to be a model semiconductor with p-type conductivity as a result of its wide band-gap energy range from 3.6 to 4.0 eV [2].…”
Section: Introductionmentioning
confidence: 99%